Development of a Model to reduce Seismic Hazards to Decrease the Vulnerability and Seismic Risk (Case study : Zanjan City, Iran) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Seismic areas, which are always at the risk of encountering earthquake crises and accidents, need recognition of risk and adaptation of human behavior to cope with probable risks. The type of attitude and adaptation of behavior, and the associated strategies include evaluations and environmental perceptions of social, economic, and cultural concepts and values, as well as individual perspectives. Seismic risk assessment can be done based on various seismic scenarios due to the vulnerability of elements exposed to risk. The seismic hazard reduction model should include the occurrence of all probable consequences in different social classes. Because of the difference among the abovementioned factors in different areas, seismic hazard reduction models cannot be the same for all zones. In this study, Zanjan City has been selected as a place to create a safe society against earthquakes. The results obtained from vulnerability and seismic risk assessment of conventional and important buildings of Zanjan have been presented in the frame of tables of urgent measures' instruction for crisis management caused by the earthquake in Zanjan. To develop the final model of seismic hazard reduction in Zanjan, 21 risky zones were identified based on vulnerability and seismic risk assessment in this city. Also, necessary measures were provided to reduce the seismic risks in four steps of earthquake crisis management including prevention, readiness, coping, and rehabilitation to reduce the hazards during 5-10 years.